Nuclear power plants? Yes or no? Thank you! The argumentative use of tables and graphs / ¿Centrales nucleares? ¿Sí o no? ¡Gracias! El uso argumentativo de tablas y gráficas. Issue 1 (2nd January 2016) - Garcia-Mila, Merce; Pérez-Echeverría, Mª Puy; Postigo, Yolanda; Martí, Eduardo; Villarroel, Constanza; Gabucio, Fernando
Abstract: The present paper deals with how eleventh grade high school students and university undergraduate students studying environmental science use evidence to write an argumentative text. They were presented with a dilemma with four sets of data (two pro and two anti nuclear energy). Half the sample was given the data in graph format and the other half in table format. The four sets of data differed according to their complexity. We analysed the structure of argument, the use of the evidence (either provided or their own) according to the participants' position on the dilemma, and the presence of confirmation bias. Our results show a good argumentative competence that does not seem to be affected either by the students' educational level or data format. We observed an effect of the complexity of the data in relation to the participants' position.